Optimization of Cutting Parameters in Rough Turning using Taguchi Method - Dhawan, Ajay P.; Shinde, Tanaji B. (Asian Review of Mechanical Engineering, 2016)
A machining process involves many process parameters which directly or indirectly influence the surface quality of the product. Current investigation on turning process is a Taguchi optimization technique applied on the most effective process parameters i.e. feed, cutting speed and depth of cut. In this project Taguchi method is used to optimize cutting parameter for surface roughness and material removal rate. The obtained results were verified by using minitab software. The optimized value of cutting speed, feed rate and depth of cut is obtained for both MRR (material removal rate) and Surface roughness. Confirmation test is carried out for the purpose of verification. Main effect plots are generated and analyzed to find out the relationship between cutting parameter and variables. The details of experimentation and analysis are given in the following context.